(untitled) (International journal of artificial intelligence, 2025)
This article explores the stages and results of transitioning from a centrally planned economy to a market-oriented system. It outlines the five major stages of the transition—macroeconomic stabilization, liberalization, privatization, institutional and legal reform, and social policy development—and explains the goals and mechanisms of each. The article also evaluates the outcomes of these reforms, highlighting both the economic successes and social challenges encountered by transitioning countries. Emphasis is placed on the diversity of national experiences and the critical role of institutions and governance in shaping results.